Are treatment guides and rational drug use policies adequately exploited in combating respiratory system diseases?. Issue 1 (January 2016) - Dogan, Mustafa; Mutlu, Levent C.; Yilmaz, İbrahim and Bilir, Bulent and Varol Saracoglu, Gamze and Yildirim Guzelant, Aliye
Summary: The aim of the present study was to increase awareness regarding the rational use of medicines. The data were obtained via the Material Resources Management System Module of the Ministry of Health. For the appropriateness of treatments, the Global Initiative for Asthma, the Global Initiative for Chronic Obstructive Lung Disease, and the guidelines for the rational use of medicines were used. We also investigated whether any de-escalation method or physical exercise was performed. Statistical analyses were performed using descriptive statistics to determine the mean, standard deviation, and frequency. The results showed that healthcare providers ignored potential drug reactions or adverse interactions, and reflecting the lack of adherence to the current treatment guides, 35.8% irrational use of medicines was recorded. Thus, de-escalation methods should be used to decrease costs or narrow the antibiotic spectrum, antibiotic selection should consider the resistance patterns, culturing methods should be analyzed, and monotherapy should be preferred over combination treatments.